Situational awareness-based energy management for unmanned electric surveillance platforms - Felix Moreno, R (Cranfield University, 2016)
In the present day fossil fuel availability, cost, security and the pollutant emissions resulting from its use have driven industry into looking for alternative ways of powering vehicles. The aim of this research is to synthesize/design and develop a framework of novel control architectures which can result in complex powered vehicle subsystems to perform better with reduced exogeneuous information. This research looks into the area of energy management by proposing an intelligent based system which not only looks at the beaten path of where energy comes from and how much of it to use, but it goes further by taking into consideration the world around it. By operating without GPS, it realies on data such as usage, average consumption, system loads and even other surrounding vehicles are considered when making the difficult decisions of where to direct the energy into, how much of it, and even when to cut systems off in benefit of others. All this is achieved in an integrated way by working within the limitations of non-fossil fuelled energy sources like fuel cells, ultracapacitors and battery banks using driver-provided information or by crafting an artificial usage profile from historicaly learnt data. By using an organic computing philosophy based on artificial intelligence this alternative approach to energy supply systems presents a different perspective beginning by accepting the fact that when hardware is set energy can be optimized only so much and takes a step further by answering the question of how to best manage it when refuelling might not be an option. The result is a situationally aware system concept that is portable to any type of electrically powered platform be it ground, aerial or marine since it operates on the fact that all operate within three dimensional space. The system´s capabilities are then verified in a virtual reality environment which can be tailored to the meet reseach needs including allowing for different altitudes, environmental temperature and humidity profiles. This VR system is coupled with a chassis dynamometer to allow for testing of real physical prototype unmanned ground vehicles where the intelligent system will benefit by learning from real platform data. The Thesis contributions and objectives are summarised next:  The control system proposed includes an awareness of the surroundings within which the vehicle is operating without relying on GPS position information.  The system proposed is portable and could be used to control other systems.  The test platform developed within the Thesis is flexible and could be used for other systems.  The control system for the fuel cell system described within the work has included an allowance for altitude and humidity. These factors would appear to be significant for such systems.  The structure of the control system and its hierarchy is novel.  The ability of the system to be applied to a UAV and as such control a ‘vehicle’ in 3 dimensions, and yet be also applied to a ground vehicle, where roll and pitch are largely a function of the ground over which it travels (so the UGV only uses a subset of the control functionality).  The mission awareness of the control structure appears to be the heart of the potential contribution to knowledge, and that this also includes the ability to create an estimated, artificial mission profile should one not be input by the operators. This learnt / adaptive input could be expanded on to highlight this aspect.